The Influence of Image Media on Learning Outcomes of Class III Students on Theme 1 Subtema 3 Animal Growth at UPTD SD Negeri 122337 Pematang Siantar - Nela Febrina Tampubolon; Yanti Arasi Sidabutar; Pdt. Esti Sirait (MultiTech Publisher, 2023)
This research aims to determine whether there is an influence of image media on the learning outcomes of class III students in Theme 1 Subtheme 3 Animal Growth at UPTD SD Negeri 122337 Pematang Siantar, the method in this research is a quantitative experimental type method whose research design is Pre-experimental type one pretest-posttest group. Conducted in October 2023, the population of all students at UPTD SD Negeri 122337 Pematang Siantar and a sample of 30 students consisting of 11 female students and 19 male students used was purposing sampling with two research variables: dependent variable (x ) in the form of learning outcomes, as well as the independent variable (y) in the form of image media . Data collection techniques are test techniques with validity tests, reliability tests, difficulty level tests, and differentiating power tests. The results of hypothesis testing using the Normality Test , and the T Test with the help of the SPSS version 2 6 program , based on the results of calculations with a significance level of α = 0.05 and db = N -1 = 30 -1 = 29, we obtain t 0.05 = 1,699. After obtaining t count = 32.669 and t table = 1.699, it can be seen that t count > t table or 32.669 > 1.699. So it can be concluded that H 0 is rejected and Ha a is accepted. This explanation shows that there is an influence of the image media type learning model on student learning outcomes for theme 1, subtheme 3, animal growth, class III, SD Negeri 122337 Pematang Siantar . This means that all independent variables have a significant influence on the dependent variable.